PENDEKATAN PENDIDIKAN KRISTIANI DALAM MENGATASI FENOMENA NARSISME DIGITAL PADA GENERASI MUDA - Kasingku, Juwinner; Winda Novita Warouw (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of social media has brought significant changes to the lives of young people, but it has also created challenges in the form of digital narcissism, namely the tendency to focus excessively on oneself and depend on social validation from others. This study aims to investigate the role of Christian Education in addressing the phenomenon of digital narcissism among young people. The research employs a qualitative approach using the Systematic Literature Review method through an examination of journals, books, and research reports published between 2015–2025 obtained from Google Scholar, Scopus, ScienceDirect, and other sources. The findings indicate that digital narcissism is influenced by several major factors, namely Fear of Missing Out (FoMO), the need for social validation, and social environmental pressures, which are reflected in behaviors such as seeking attention, excessive self-presentation, and dependence on others’ responses on social media. In addressing this phenomenon, Christian Education plays a role through three main approaches: the use of digital media in accordance with biblical principles, reflective and transformational education, and pastoral mentoring for young people. These three approaches help shape a strong identity, foster Christian character, and encourage responsible use of digital media. This study emphasizes that collaboration between education, the church, and spiritual mentoring is an important step in helping young people overcome digital narcissism, grow in faith, and develop strong character amid the challenges of the digital era.